Interleukin-6 in old patients with trophic ulcers of the lower extremities - Svetlana V. Topolyanskaya; Leonid I. Bubman; Viktor V. Karpov; Stanislav O. Khan; Aleksei I. Nechaev; Yulia Yu. Vasilyeva; Karine A. Lytkina; Georgii G. Melkonyan; Svetlana A. Ratchina; Leonid I. Dvoretski (LLC "MEDIAFORMAT", 2023)
Aim. To study the pathogenetic role of interleukin-6 (IL-6) in old patients with trophic ulcers of the lower extremities. Methods. The study enrolled 66 patients suffered from trophic ulcers of the lower extremities. The mean age of study patients reached 77.1±9.1 years (62-97 years). The majority of patients (65.1%) were women. The concentration of IL-6 in the blood (n<7.0 pg/ml) was determined by enzyme immunoassay. Results. Increased level of IL-6 was found in 77.3% of patients. The mean concentration of IL-6 was 14.9±14.6 pg/ml (1.5-288.6 pg/ml), median - 10.7pg/ml. The mean values of interleukin-6 in patients with venous ulcers reached 12.7 pg/ml, arterial - 13.4 pg/ml, mixed - 26.7 pg/ml (p=0.01). Direct correlation was registered between IL-6 level and the number of ulcers (r=0.3; p=0.02). There was a direct correlation between IL-6 concentration and the ulcers duration (r=0.28; p=0.03). There was a trend towards a direct correlation between interleukin-6 and ulcers size (r=0.23; p=0.08). In patients with infected ulcers, the mean IL-6 level was 17.5 pg/ml, in patients without microbiological growth - 11.6 pg/ml, but these differences did not reach the statistical significance (p=0.3). Significant direct correlations were established between IL-6 concentration and the level of C-reactive protein (r=0.61; p<0.000001), leukocyte count (r=0.36; p=0.006), neutrophil count (r=0.39; p=0.002), platelet count (r=0.39; p=0.002), ESR (r=0.40; p=0.003), inverse correlation - with hemoglobin (r=-0.41; p=0.001). There was a direct correlation between IL-6 level and severity of frailty (r=-0.38; p=0.03) and inverse correlation - with instrumental activity in daily life scale (r=-0.35; p=0.03). Patients with elevated IL-6 concentration had higher CRP (18.3 and 6.7 mg/l; p=0.001) and ESR (42.5 and 28.1 mg/l; p=0.04mm/h), but lower hemoglobin levels (114.3 and 125.9 g/l; p=0.01). There was a tendency to a direct correlation between IL-6 level and the age of study patients (r=0.23; p=0.06). Conclusion. Study results indicate a frequent increase in the interleukin-6 level in old patients with trophic ulcers of lower extremities. An increase in IL-6 concentration is associated with number and duration of ulcers as well as with various hematological parameters.